ANALISA KOMPARATIF MODEL PREDIKSI KEBANGRUTAN ALTMAN Z-SCORE & ZMIJEWSKI PADA PERUSAHAAN BUMN SEBELUM, SELAMA & SESUDAH PANDEMI COVID-19 - Ninuk Riesmiyantiningtias; Rizky Amalia; Abdurrachman Abdurrachman; Alan Budi Kusuma (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
This study aims to analyze bankruptcy prediction using the Altman Z-Score and Zmijewski methods for state-owned enterprises (BUMN) listed on the IDX. This research is a comparative descriptive study by comparing the Financial Distress measurement model using the Z-Score Altman and Zwijewski models before, during and after the Covid-19 Pandemic. The results of the study concluded that with the Altman Z-Score and Zmijewski models there was an increase in BUMN companies that were predicted to go bankrupt prior to the Covid-19 Pandemic. After the Covid-19 Pandemic, state-owned companies experienced improved financial performance so that there was an increase in healthy companies, although not significant